تقييم فعالية تقنية موهلر في الإصلاح الأولي لشق الشفة أحادي الجانب - خليل عبد الكريم; حسين عبد المولى (Latakia University Journal -Medical Sciences Series, 2017)
هدفت هذه الدراسة إلى تقييم فعالية تقنية موهلر في الإصلاح الجراحي الأولي لشق الشفة الأحادي الجانب. تألفت عينة البحث من12حالة راجعت قسم جراحة الفم و الفكين في مشفى الأسد الجامعي،مع شق شفة كامل أحادي الجانب, في الفترة ما بين1 نيسان 2014 و1 نيسان 2015.تضمنت المراقبة السريرية أخذ صور فوتوغرافية للمرضى بالوضعية الأمامية لتقييمتناظر ارتفاع الشفة الجلدية و بالوضعية الأنفية الجبهية لتقييم تناظر فتحتي الأنف بين الجانب المشقوق والجانب غير المشقوق بعد 15 يوم و 6 أشهر من العمل الجراحي. أظهرت النتائج فروق ذات دلالة احصائية خلال فترة المتابعة التي استمرت 6 أشهر بعد العمل الجراحي, حيث كانت نسبة اختلاف ارتفاع الشفة الجلدية 6.17% بعد 6 أشهر في حين كانت22.58%بعد 15 يوم من العمل الجراحي(قيمة مستوى الدلالة <0,01). وكانت نسبة عدم تناظر فتحتي الأنف 8.25% بعد 6 أشهر من العمل الجراحي في حين كانت 15.08% بعد 15 يوم من العمل الجراحي (قيمة مستوى الدلالة <0,01).أظهرت نتائجهذه الدراسةتحسن تناظر ارتفاع الشفة الجلدية و تناظر فتحتي الانف عند استخدام تقنية موهلر في الإصلاح الجراحي الأولي لشق الشفة الكاملالأحادي الجانب. The aim of this study was to assessment the effect of using MohlerTechnique in primary repair ofunilateral cleft lip. The study comprised of12cases attendedto department of oral and maxillofacial surgery at Alassad University HospitalLattakia-Syria, with completeunilateral cleft lip between 1 April 2014 and 1 April 2015. The clinical observation included taking photographs for the patients in anterior position to evaluate symmetry of cutaneous lip heights and in naso-frontal position to evaluate symmetry of nostrils between the cleft side and noncleft side at 15 days and 6 months postoperative. The results showed a significance statistical difference during the follow up to 6 months postoperative; as the measured percentage of the cutaneous lip height difference was 6.17% after 6 months from surgery while it was 22.58% 15 days postoperative (P<0.01). Percentage of nostrils asymmetry was 8.25% after 6 months from surgery while it was 15.08% 15 days postoperative (P<0.01).Theresults of this study demonstrated cutaneous lip height symmetry and nostrils symmetry improvement by using MohlerTechnique in primary repair ofcomplete unilateral cleft lip.